2022
DOI: 10.1186/s12936-022-04154-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on malaria cases in health facilities in northern Ghana: a retrospective analysis of routine surveillance data

Abstract: Background The COVID-19 pandemic and its collateral damage severely impact health systems globally and risk to worsen the malaria situation in endemic countries. Malaria is a leading cause of morbidity and mortality in Ghana. This study aims to describe the potential effects of the COVID-19 pandemic on malaria cases observed in health facilities in the Northern Region of Ghana. Methods Monthly routine data from the District Health Information Manag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 22 publications
(25 reference statements)
2
37
0
Order By: Relevance
“…[16] In contrast, a study in Ghana that compared similar periods observed a reduction in the cases of malaria among under-ve. [14] In Rwanda, a study that also compared similar periods like this current study did observe any change in the cases of severe malaria. [15] It is worthy of note that the site of this present study falls under the malaria endemic zone in Nigeria, with high seasonal variability.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…[16] In contrast, a study in Ghana that compared similar periods observed a reduction in the cases of malaria among under-ve. [14] In Rwanda, a study that also compared similar periods like this current study did observe any change in the cases of severe malaria. [15] It is worthy of note that the site of this present study falls under the malaria endemic zone in Nigeria, with high seasonal variability.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, a retrospective study in northern Ghana that compared pre-COVID-19 and COVID-19 periods showed a decline in malaria cases at health facilities. [14] A similar study in the malaria endemic part of Rwanda found no change in the overall rate of uncomplicated malaria with a reduction in the proportion of severe malaria cases at the health facilities. [15] In Zimbabwe, when compared with the pre-COVID-19 period, COVID-19 was associated surge in malaria cases and deaths.…”
mentioning
confidence: 92%
“…The ongoing COVID-19 pandemic may also impact the probability that a patient is tested if they seek care for their illness (e.g., malaria, HIV, Tuberculosis, other infectious and chronic diseases). Factors that may influence the likelihood of testing include symptom presentation, prevalence of the illness, availability of testing or treatment supplies, the ability of the health facility to manage COVID-19 as well as other common diseases, amongst others ( 9 , 10 ). A study in Rwanda found that there was a reduction in malaria testing at health facilities during the pandemic but increases in community-based testing ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Malaria parasite prevalence among children aged 6–59 months in the 2011 report indicated a regional variation from as low as 4% in the Greater Accra region to as high as 51% in the Upper West region [ 21 ]. Malaria remains the number one cause of OPD attendance and the first among the top ten diseases in Ghana [ 22 ]. The National Malaria Control Program (NMCP) in collaboration with the Upper West Regional Health Directorate (RHD) and Sissala East Municipal Health Directorate (MHD) continue to implement interventions across the municipality aimed at controlling the burden of the disease within the municipality, region and Ghana as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…The National Malaria Control Program (NMCP) in collaboration with the Upper West Regional Health Directorate (RHD) and Sissala East Municipal Health Directorate (MHD) continue to implement interventions across the municipality aimed at controlling the burden of the disease within the municipality, region and Ghana as a whole. These interventions include Long-lasting insecticidal nets (LLIN) distribution, In-door Residual Spraying and Seasonal Malaria Chemoprevention (SMC) among others [ 22 ].…”
Section: Introductionmentioning
confidence: 99%